Ideas for Development - Chambers, Robert (Routledge, 2005)
Our world seems entangled in systems increasingly dominated by power, greed, ignorance, self-deception and denial, with spiralling inequity and injustice. Against a backdrop of climate change, failing ecosystem s, poverty, crushing debt and corporate exploitation, the future of ou r world looks dire and the solutions almost too monumental to consider . Yet all is not lost. Robert Chambers, one of the ?glass is half full ? optimists of international development, suggests that the problems c an be solved and everyone has the power at a personal level to take ac tion, develop solutions and remake our world as it can and should be. Chambers peels apart and analyses aspects of development that have bee n neglected or misunderstood. In each chapter, he presents an earlier writing which he then reviews and reflects upon in a contemporary ligh t before harvesting a wealth of powerful conclusions and practical imp lications for the future. The book draws on experiences from Africa, A sia and elsewhere, covering topics and concepts as wide and varied as irreversibility, continuity and commitment; administrative capacity as a scarce resource; procedures and principles; participation in the pa st, present and future; scaling up; behaviour and attitudes; responsib le wellbeing; and concepts for development in the 21st century.